Learning Interest in Elementary Science Education: A Descriptive Study of the Attention–Engagement Divergence Among Fifth-Grade Students in Rural Indonesia - Azzahra Zahwa Adillah; Sisriawan Lapasere; Pahriadi Pahriadi; Surahman Surahman (Journal of Innovation and Research in Primary Education, 2026)
Learning interest is a multidimensional psychological construct that critically shapes students’ academic engagement and outcomes in elementary science education. Empirical evidence on its disaggregated indicator profile in Integrated Natural and Social Sciences (IPAS) under Indonesia’s Independent Curriculum remains limited, particularly in rural school contexts. This descriptive quantitative study examined learning interest among 15 fifth-grade students at Porame State Elementary School, Sigi Regency, Central Sulawesi. Data were collected via a validated 20-item Likert-scale questionnaire (Cronbach’s α = 0.81) across four indicators: subject interest, student attention, feelings of enjoyment, and active engagement, analyzed using univariate percentage analysis. The overall learning interest score was 72.75% (high), with attention reaching the very high level (88.33%), while subject interest (67.33%), enjoyment (68.00%), and active engagement (67.33%) each fell in the moderate range. Notably, only 46.66% of students studied independently in the teacher’s absence. This attention–engagement divergence suggests that high behavioral compliance does not necessarily reflect deep affective or autonomous engagement, a pattern characteristic of teacher-centered instructional contexts. Findings contribute to the reconceptualization of learning interest as an asymmetrically developing construct and call for inquiry-based, locally contextualized IPAS instruction to foster genuine student engagement.